Electrostatic charging at the solid-liquid interface: Strategies for liquid flow sensing - Campo, Yan Araujo Santos da; Moreira, Kelly Schneider; Lorenzett, Ezequiel; Burgo, Thiago Augusto Lima [UNESP] (Tsinghua Univ Press, 2025)
A particular kind of triboelectrification occurs during the flow of liquids through tubes. Here, we used Faraday cups and Kelvin probes to investigate the charge of aqueous solutions and alcohols flowing through a polytetrafluorethylene tube. An excess of positive charges was observed in all liquids collected by the Faraday cup after the flow. While the tube displays a small potential during the flow, likely due to electrokinetic effects, a very high negative potential was observed after the completion of the flow. Aqueous solutions with varying pH showed significant differences in charge accumulation only at pH 2.93 and 4.99, while most of the charge accumulation can be suppressed using common surfactants. Alcohols displayed an inverse relationship between charge accumulation and carbon chain length, except for methanol. Thus, we used graphite-based nanocomposites as noncontact induction electrodes near the tube for flow sensing. A proof of concept was conducted using these induction electrodes to differentiate between water and ethanol flowing inside the tube, which was repeated thousands of times. Finally, the output voltage signal from the induction electrode was processed through an input signal filter and a microcontroller, where four lightemitting diodes (LEDs) were incorporated to indicate the flow and type of liquid.
Keywords: contact charging; flow electrification; sensors; solid-water interface; nanocomposite; electric double layer